Refocusing adult education in conformity with fundamental changes of modern realties (2016)
The growing importance of adult education as a major instrument for achieving sustainable lifelong learning in various spheres of human endeavours have led to fundamental changes in its structure and tenets. Based on these changes, this paper, therefore, provided a strong justification for refocusing the structures and tenets of adult education in conformity with fundamental changes of modem realties. The paper began with a critical dissection of the cardinal areas where fundamental changes have occurred in adult education. Such areas include: the new understanding and definitions of adult education, the new roles and objectives of Adult Education, the expanded components of Adult Education, the expanded philosophical approach of adult education, the expanded learning environment (ELE), the expanded views of the rationale behind educating them, and the expanded perceptions of the commonly accepted beliefs regarding adult education. The paper was concluded with some recommendations on the strategies for reshaping the structures and tenets of adult education in Nigeria in order to make the discipline conforms to these documented changes